A case report of a congenital cleft of the anterior atlas arch: a rare variant of the atlas mimicking fracture - van der Velde, Gabrielle M (1997)
Congenital anterior midline clefts of the atlas are rare developmental anomalies with only a few reported cases in the literature. This normal variant of the atlas results when the anterior arch fails to fuse during the ossification process. Series of cadaveric dissections have demonstrated anterior midline atlas clefts in 0.1-0.2% of the general population. Histological examinations have revealed that the bony defect, which ranges from 1-5 millimetres in width, is bridged by fibrocartilagenous tissue, resulting in what is generally believed to be a stable atlas. Radiographically, congenital anterior clefts mimic many types of atlantal fractures, including Jefferson burst fractures, and vertical fractures of the anterior arches. The distinct radiographic appearances of congenital clefts and acute fractures of the atlas help to distinguish them from each other. In the majority of cases, anterior clefts of the atlas remain undetected and have no clinical ramifications. Detection usually occurs during emergency post-traumatic radiographic imaging of the upper cervical spine. Under these circumstances, the presence of this congenital anomaly can make it difficult to differentiate between an acute fracture and a congenital variant. Where there is suspicion of fracture, computed tomography (CT) must be considered, as it is the most useful means of differentiating between these two clinical entities. Chiropractors considering spinal manipulative therapy should be concerned with stability of an atlas with an anterior cleft, particularly in patients with a recent history of injury to the cervical spine. Appropriate clinical and radiographic examinations must be used to rule out cervical spine instability, before treatment is commenced. A reasonable course of treatment may include the judicious use of spinal manipulation.